2012
DOI: 10.1016/j.neuron.2012.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Dopamine Release Is Triggered by Synchronized Activity in Cholinergic Interneurons

Abstract: Striatal dopamine plays key roles in our normal and pathological goal-directed actions. To understand dopamine function, much attention has focused on how midbrain dopamine neurons modulate their firing patterns. However, we identify a presynaptic mechanism that triggers dopamine release directly, bypassing activity in dopamine neurons. We paired electrophysiological recordings of striatal channelrhodopsin2-expressing cholinergic interneurons with simultaneous detection of dopamine release at carbon-fiber micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
840
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 729 publications
(920 citation statements)
references
References 31 publications
42
840
9
1
Order By: Relevance
“…However, dopamine, acting via D1/D5 receptors, potentiates the excitability of cholinergic neurons and their responsiveness to glutamatergic input 28. It has been also shown that the release of endogenous acetylcholine is sufficient to promote dopamine release via nAChR activity without activation of dopaminergic neurons 29. Therefore, presynaptic nAChRs on dopamine terminals appear to have different modulatory influences on dopamine release, one via activity of dopamine neurons and the other via thalamo‐striatal glutamate activity through cholinergic interneurons independent of the actual dopamine neuron activity 26, 28.…”
Section: Discussionmentioning
confidence: 99%
“…However, dopamine, acting via D1/D5 receptors, potentiates the excitability of cholinergic neurons and their responsiveness to glutamatergic input 28. It has been also shown that the release of endogenous acetylcholine is sufficient to promote dopamine release via nAChR activity without activation of dopaminergic neurons 29. Therefore, presynaptic nAChRs on dopamine terminals appear to have different modulatory influences on dopamine release, one via activity of dopamine neurons and the other via thalamo‐striatal glutamate activity through cholinergic interneurons independent of the actual dopamine neuron activity 26, 28.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in the field of neurochemistry now explain the bidirectional effect of nicotine on stimulated dopamine release in the dorsal striatum. Whilst it has recently been elegantly shown that dopamine release driven by action potential firing in dopaminergic axons alone is insensitive to nicotine, nicotine selectively blocks ChI-induced dopamine release [7]. Nicotine selectively blocked the ChI pathway by desensitizing α6β2*nAChRs on the dopaminergic terminals, which caused the inhibition of dopamine release following a single pulse (representing low Dopamine)release) (%)control)) Dopamine)release)))) (%)peak)single)pulse))…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine can also cause short-term facilitation of dopamine release at the second and the third pulses in the 20 Hz burst of stimuli (mimicking high-frequency phasic firing) because blockade of the ChI pathway reduced the depletion of the dopamine vesicle pool at the first pulse in a train [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this approach, the driver transgene defines the cell types, and the injection of virus provides regional specificity. For example, in order to target cholinergic interneurons, viruses encoding Cre-dependent genetic tools were injected into various brain regions of a mouse line that encodes Cre under the control of choline acetyltransferase promoter [91,97,98]. Although strong Cre expression is found in multiple brain regions, including striatum, brain stem, and hippocampus [83,84,[98][99][100][101], the expression of genetic tools was restricted only in the brain regions targeted with viral injection [91,97,98].…”
Section: Combining Genetic Identity and Spatial Controlmentioning
confidence: 99%